Choosing the Currency Structure for Sovereign Debt : A Review of Current Approaches - Melecky, Martin (World Bank, Washington, DC, 2012)
This paper acknowledges the fact that some countries have to borrow in foreign currencies due to the various constraints they face. Starting from this point, the author reviews approaches for trying to determine the currency structure for sovereign debt, and discusses some issues inherent in these approaches. The analysis mainly focuses on the correlations of domestic fundamentals with the actual versus equilibrium exchange rate in light of the long-term perspective of a debt manager and changing exchange rate regimes. In addition, the author makes some observations on the characterization of exchange rate volatilities in the existing approaches.